GEOGRAPHIC VARIATION OF CHLOROPLAST DNA HAPLOTYPES IN Acacia aulacocarpa A. Cunn. ex Benth - Widyatmoko, Anthonius Y.P.B.C.; Shiraishi, Susumu (Secretariat of Forestry Research and Development Agency, 2013)
The geographic variation of chloroplast DNA (cpDNA) haplotypes of Acacia aulacocar pa was investigated among 18 natural populations. These populations represent the geographical range of the species in New Guinea Island and Queensland. Single strand conformation polymorphism (SSCP) was used for the analysis. Two non-coding regions of cpDNA, the intron region of the trnL gene and the intergenic spacer region between the trnP and trnW genes, were analyzed, and four haplotypes (A, B, C, and D) were recognized. The haplotype distribution corresponded with the geographic distribution of the populations. Based on four cpDNA haplotypes, the eighteen populations were divided into three groups: New Guinea Island, Northern Queensland and Southern Queensland. Haplotype C was observed only in the New Guinean populations, while the other three haplotypes (A, B, and D) were found in Queensland only. All of these three haplotypes were observed in Southern Queensland, whereas haplotype B was found only in the Northern Queensland populations. The cpDNA haplotype diversity of this species seemed to be highest in southern Queensland.